Laboratory Model Tests on Consolidation Performance of Soil Column with Drained-Timber Rod. (22nd March 2021) - Chai, X. J.; Deng, K.; He, C. F.; Xiong, Y. F.
Abstract : Timber pile is an ancient technology applied in soft ground improvement for more than 1000 years. With the rise of many high-rise buildings, many types of modern mechanized-construction piles are widely developed and applied; for example, steel pile, precast concrete pile, sand pile, and gravel pile are widely used instead of timber piles. Yet, in some special conditions, timber piles have certain advantages due to their environment-friendly characteristics, which result in obvious economic benefits and suitability. To overcome the weakness of the traditional timber pile technology and expand its application in engineering practice, a drained-timber pile technique was put forward. This technology is to wrap the permeable filter-type drainage geotextile around the timber pile, so that the timber pile not only has the replacement function to strengthen the foundation but also has the drainage function, can accelerate the pore water discharge, and speeds up the soft soil foundation consolidation. The reduced scale soil-column consolidation model was designed to perform the consolidation tests for the soil column with a drained-timber rod. In total, eight types of soil-column consolidation tests were carried out to verify the feasibility and effectiveness of the drained-timber pile technique. The results revealed that, under the same loading and consolidation time, the drained-timber rod can obviously increase the degree of consolidation when compared with traditional timber rod. It can be expected that the drained-timber pile technique has a good application prospect for the construction of medium-small hydraulic structures and for the treatment of super soft clay.